Effects of ground raw candlenut (Aleurites Moluccana (L.} Willd) Kernel on growth performance in quail - Mohd Afiq Nur Adamin (Universiti Malaysia Sabah, 2017)
The experiment was carried out to determine the effects of ground raw candlenut kernel at different levels (%) on the growth performance of broiler quails in the Poultry Unit at Faculty of Sustainable Agriculture, Universiti of Malaysia Sabah, Sandakan campus. The birds were allocated into four treatment groups, each replicated five times, consisting of 5 birds each in a Completely Randomized Design (CRD). Started from day 21 onwards, the birds were fed with either one of the four dietary treatments (Table 1.2), namely; (Tl) basal diet (BD); (T2) basal diet + 2.Sg/kg ground raw candlenut kernel (0.25%); (T3) basal diet + Sg/kg ground raw candlenut kernel (0.50%); and (T4) basal diet + 10 g/kg ground raw candlenut kernel (1%). All diets have been isonitrogenous formulated to meet or exceed the NRC (1994) requirement, and was offered in the mash form. Parameters such as body weight (g), daily weight gain (g), feed intake (g), feed conversion ratio (FCR) and mortality of broiler quails were assessed in this experiment. Proximate analysis and fatty acid composition were also analyzed in this experiment. All the data collected were arranged in the form of Microsoft Excel 2010 as the basement data and the data were used again in the form of arrangement data by using Statistical Analysis System (SAS) v9.4. The growth performances were not significantly {p>0.05) affected by the ground raw candlenut kernel. The fatty acid composition analyzed were also had no significant (p>0.05) effects by the ground raw candlenut kernel. However, there were significant differences (p<0.05) on proximate analysis which include dry matter(%), ash(%), crude fibre(%) and crude fat(%) except for gross energy (MJ/kg). The best treatment was shown in T4 which has the least value of feed conversion ratio (FCR) which indicates a better feed efficiency compared to other treatments. The experiment was carried out to determine the effects of ground raw candlenut kernel at different levels (%) on the growth performance of broiler quails in the Poultry Unit at Faculty of Sustainable Agriculture, Universiti of Malaysia Sabah, Sandakan campus. The birds were allocated into four treatment groups, each replicated five times, consisting of 5 birds each in a Completely Randomized Design (CRD). Started from day 21 onwards, the birds were fed with either one of the four dietary treatments (Table 1.2), namely; (Tl) basal diet (BD); (T2) basal diet + 2.Sg/kg ground raw candlenut kernel (0.25%); (T3) basal diet + Sg/kg ground raw candlenut kernel (0.50%); and (T4) basal diet + 10 g/kg ground raw candlenut kernel (1%). All diets have been isonitrogenous formulated to meet or exceed the NRC (1994) requirement, and was offered in the mash form. Parameters such as body weight (g), daily weight gain (g), feed intake (g), feed conversion ratio (FCR) and mortality of broiler quails were assessed in this experiment. Proximate analysis and fatty acid composition were also analyzed in this experiment. All the data collected were arranged in the form of Microsoft Excel 2010 as the basement data and the data were used again in the form of arrangement data by using Statistical Analysis System (SAS) v9.4. The growth performances were not significantly {p>0.05) affected by the ground raw candlenut kernel. The fatty acid composition analyzed were also had no significant (p>0.05) effects by the ground raw candlenut kernel. However, there were significant differences (p<0.05) on proximate analysis which include dry matter(%), ash(%), crude fibre(%) and crude fat(%) except for gross energy (MJ/kg). The best treatment was shown in T4 which has the least value of feed conversion ratio (FCR) which indicates a better feed efficiency compared to other treatments.